Advanced Information Systems Engineering Workshops : CAISE 2016 International Workshops, Ljubljana, Slovenia, June 13-17, 2016, proceedings /: CAISE 2016 International Workshops, Ljubljana, Slovenia, June 13-17, 2016, proceedings. (2016) - Unknown
No abstract available